Ni / SiO2 catalyst and preparation method thereof
By synthesizing and processing a precursor with a nickel phyllosilicate structure, a Ni/SiO2 catalyst is prepared, which solves the problems of high cost and poor reaction activity of existing precious metal catalysts, achieves low-cost and efficient hydrogenation of waste plastics, and obtains high selection The sexual products CH4 and HCl.
Patent Information
- Application Number
- CN202310887206.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2023-07-19
- Publication Date
- 2025-01-21
AI Technical Summary
The existing precious metal catalysts have high cost, poor reactivity and stability in the hydrogenolysis process of waste plastics, and the carbon number distribution of the products obtained by base metal catalysts is relatively wide, so the subsequent separation is complicated.
A Ni/SiO2 catalyst is developed. By synthesizing a precursor with a nickel phyllosilicate structure, and subjecting it to roasting and pre-reduction treatment, a Ni/SiO2 catalyst with a Ni loading of 1-30wt% is obtained.
It achieves low-cost, efficient and highly selective hydrogenolysis of mixed waste plastics to CH4 and other chemical raw materials, with excellent reactivity, high stability and good HCl tolerance.
Smart Images

Figure BDA0004346652490000071 
Figure BDA0004346652490000081
Abstract
Description
Technical Field
[0001] The present application relates to the technical field of catalytic materials, and in particular to a Ni / SiO2 catalyst and a preparation method thereof. Background Art
[0002] The hydrogenolysis of waste plastics can produce alkanes, aromatics or other high-value chemicals with different carbon numbers, and has become an important conversion path. However, the current hydrogenolysis catalysts are mainly concentrated on precious metal-loaded catalysts such as Pt and Ru. Precious metal catalysts can efficiently cut polyolefins into CH4 or alkanes of different chain lengths, but there are also many problems: 1. The price of precious metals is relatively high, and the amount of catalyst feed is large during the conversion of waste plastics, resulting in huge catalyst costs and the inability to scale up the recycling process; 2. Precious metal catalysts such as Pt and Ru are easily poisoned by elements such as Cl contained in mixed plastics, resulting in poor reactivity and stability. Although the base metal catalysts (such as Co-based catalysts) and molecular sieve catalysts currently used for hydrogenolysis are cheap and easy to obtain, they mainly produce mixed alkanes and aromatics with a wide carbon number distribution, and the subsequent separation process is complicated. Therefore, the development of low-cost, inexpensive catalysts that can efficiently and selectively obtain single products is a major problem that needs to be overcome in the recycling of waste plastics. Summary of the invention
[0003] The purpose of this application is to provide a Ni / SiO2 catalyst and a preparation method thereof, so as to obtain a low-cost Ni-based catalyst that can efficiently and selectively hydrogenate mixed waste plastics into CH4 and other chemical raw materials. The specific technical solution is as follows:
[0004] In a first aspect, the present application provides a Ni / SiO2 catalyst, wherein the loading amount of Ni in the Ni / SiO2 catalyst is 1-30wt%.
[0005] The second aspect of the present application provides a method for preparing the Ni / SiO2 catalyst provided in the first aspect of the present application, comprising:
[0006] (1) dissolving Ni(NO3)2·6H2O and Si(OC2H5)4 in an 85-95 vol% ethanol aqueous solution, then heating to 70-90°C, adding an ammonium carbonate solution with a concentration of 0.4-0.6 mol / L, and controlling the pH to 8-9, reacting for 2-6 hours, so that Ni and Si are precipitated to form a solid having a nickel phyllosilicate structure, washing with water, and drying to obtain a precursor of a Ni / SiO2 catalyst;
[0007] Among them, the ratio of the mass of Ni(NO3)2·6H2O, the mass of Si(OC2H5)4, the volume of ethanol aqueous solution, and the volume of ammonium carbonate solution is (0.01-0.45) g: 1 g: (20-60) mL: (5-40) mL;
[0008] or,
[0009] (1') under stirring, a Ni(NO3)2·6H2O aqueous solution with a concentration of 0.01-0.4 g / mL is added dropwise to a SiO2 dispersion with a concentration of 0.04-0.1 g / mL, followed by ultrasonic treatment for 4-6 minutes; the suspension is then freeze-dried to obtain a Ni / SiO2 catalyst precursor;
[0010] (2) Taking the precursor of the Ni / SiO2 catalyst, calcining and pre-reducing it to obtain the Ni / SiO2 catalyst.
[0011] The present application provides a Ni / SiO2 catalyst and a preparation method thereof. The Ni loading amount in the Ni / SiO2 catalyst is 1-30wt%. A precursor having a nickel sheet silicate (NiSiO3) structure is synthesized, and then subjected to calcination, pre-reduction and other treatments to obtain a Ni-based catalyst having high efficiency in hydrogenolysis of waste plastics: a Ni / SiO2 catalyst. The catalyst has excellent reaction activity, high stability and good HCl tolerance, and has the advantages of low cost while being able to realize high efficiency and high selectivity in hydrogenolysis of mixed waste plastics into CH4 and other chemical raw materials (such as HCl, H2O, NH3, etc.). DETAILED DESCRIPTION
[0012] The technical solutions in the embodiments of the present application are described clearly and completely below. Obviously, the described embodiments are only part of the embodiments of the present application, not all of the embodiments. Based on the embodiments in the present application, all other embodiments obtained by ordinary technicians in this field based on the present application belong to the scope of protection of the present application.
[0013] In a first aspect, the present application provides a Ni / SiO2 catalyst, wherein the Ni loading amount in the Ni / SiO2 catalyst is 1-30wt%; preferably, the Ni loading amount is 5-20wt%.
[0014] In some embodiments of the first aspect of the present application, in the Ni / SiO2 catalyst, the Ni dispersion is ≥30%, and the Ni particle size is 5-10 nm.
[0015] The second aspect of the present application provides a method for preparing the Ni / SiO2 catalyst provided in the first aspect of the present application, comprising:
[0016] (1) dissolving Ni(NO3)2·6H2O and Si(OC2H5)4 in an 85-95 vol% ethanol aqueous solution, then heating to 70-90°C, adding an ammonium carbonate solution with a concentration of 0.4-0.6 mol / L, and controlling the pH to 8-9, reacting for 2-6 hours, so that Ni and Si are precipitated to form a solid having a nickel phyllosilicate structure, washing with water, and drying to obtain a precursor of a Ni / SiO2 catalyst;
[0017] The ratio of the mass of Ni(NO3)2·6H2O, the mass of Si(OC2H5)4, the volume of ethanol aqueous solution, and the volume of ammonium carbonate solution is (0.01-0.45) g: 1 g: (20-60) mL: (5-40) mL; preferably (0.05-0.3) g: 1 g: (40-60) mL: (5-40) mL;
[0018] or,
[0019] (1') under stirring, adding a Ni(NO3)2·6H2O aqueous solution with a concentration of 0.01-0.4 g / mL dropwise to a SiO2 dispersion with a concentration of 0.04-0.1 g / mL, and then ultrasonically treating for 4-6 minutes; then freeze-drying the suspension to obtain a Ni / SiO2 catalyst precursor; preferably, the Ni(NO3)2·6H2O aqueous solution has a concentration of 0.05-0.3 g / mL;
[0020] (2) Taking the precursor of the Ni / SiO2 catalyst, calcining and pre-reducing it to obtain the Ni / SiO2 catalyst.
[0021] The Ni / SiO2 catalyst with a Ni loading of 1-30wt% prepared by the preparation method of the present application can hydrogenolyze mixed waste plastics (including PE, PP, and PVC). Preferably, the Ni / SiO2 catalyst with a Ni loading of 5-30wt% can achieve almost complete conversion of waste plastics (such as plastic conversion rate > 99%), and can highly selectively obtain CH4 (CH4 yield ≥98%) and HCl (HCl yield ≥99%); at the same time, the Ni / SiO2 catalyst also has excellent resistance to HCl poisoning and has good stability during the conversion process of the waste plastic system.
[0022] In some embodiments of the second aspect of the present application, the calcination includes high-temperature calcination at 350-550°C for 3-6h; preferably, the calcination temperature is 450-550°C, more preferably 480-520°C.
[0023] In some embodiments of the second aspect of the present application, the pre-reduction comprises: 20-80 mL / min of H2 at 200-600°C for 1-6 h; preferably, the pre-reduction comprises: 30-60 mL / min of H2 at 300-500°C for 2-5 h.
[0024] In some embodiments of the second aspect of the present application, the precursor of the Ni / SiO2 catalyst is a precursor having a nickel phyllosilicate structure.
[0025] In the present application, a highly efficient mixed waste plastic hydrogenolysis catalyst is prepared using a precursor with a NiSiO3 nickel silicate structure: a Ni / SiO2 catalyst with a Ni loading of 1-30wt%. The structure of its precursor NiSiO3 can not only achieve a high degree of Ni dispersion and improve the utilization efficiency of the metal, but also stabilize Ni clusters or particles that are easily agglomerated at high temperatures, so that the catalyst has higher activity and better stability.
[0026] The following examples are given to more specifically illustrate the implementation methods of the present application. The experimental materials and methods used in the following examples are conventional materials and methods unless otherwise specified.
[0027] Example 1
[0028] Dissolve 0.10g of Ni(NO3)2·6H2O in 8mL of deionized water; disperse 2g of SiO2 in 25mL of water and disperse evenly by ultrasonication. Add Ni(NO3)2·6H2O dropwise to the SiO2 dispersion under stirring, and ultrasonicate for 5 minutes; then freeze-dry the suspension to obtain a Ni / SiO2 catalyst precursor;
[0029] The catalyst was calcined at 500°C for 4 h and pre-reduced with 40 mL / min of H2 at 500°C for 2 h to obtain a Ni / SiO2 catalyst with a Ni content of 1 wt%.
[0030] Example 2
[0031] 0.25 g of Ni(NO3)2·6H2O and 3.46 g of Si(OC2H5)4 were dissolved in 50 mL of 90 vol% ethanol aqueous solution, and then heated to 80°C, 8 mL of 0.5 mol / L ammonium carbonate solution was added dropwise, and the pH was controlled to be 8.5. The reaction time was 4 h, so that Ni and Si were precipitated and a solid with a nickel phyllosilicate structure was formed, which was then washed with water and dried to obtain a precursor with a nickel phyllosilicate structure;
[0032] The catalyst was calcined at 500°C for 4 h and pre-reduced with 40 mL / min of H2 at 500°C for 2 h to obtain a Ni / SiO2 catalyst with a Ni content of 5 wt%.
[0033] Example 3
[0034] 0.49 g of Ni(NO3)2·6H2O and 3.46 g of Si(OC2H5)4 were dissolved in 50 mL of 90 vol% ethanol aqueous solution, and then heated to 80°C, 18 mL of 0.5 mol / L ammonium carbonate solution was added dropwise, and the pH was controlled to be 8.5. The reaction time was 4 h, so that Ni and Si were precipitated and a solid with a nickel phyllosilicate structure was formed, which was then washed with water and dried to obtain a precursor with a nickel phyllosilicate structure;
[0035] The catalyst was calcined at 500°C for 4 h and pre-reduced with 40 mL / min of H2 at 500°C for 2 h to obtain a Ni / SiO2 catalyst with a Ni content of 10 wt%.
[0036] Example 4
[0037] 0.98 g of Ni(NO3)2·6H2O and 3.46 g of Si(OC2H5)4 were dissolved in 50 mL of 90 vol% ethanol aqueous solution, and then heated to 80°C, 35 mL of 0.5 mol / L ammonium carbonate solution was added dropwise, and the pH was controlled to be 8.5. The reaction time was 4 h, so that Ni and Si were precipitated and a solid with a nickel phyllosilicate structure was formed, which was then washed with water and dried to obtain a precursor with a nickel phyllosilicate structure;
[0038] The catalyst was calcined at 500°C for 4 h and pre-reduced with 40 mL / min of H2 at 500°C for 2 h to obtain a Ni / SiO2 catalyst with a Ni content of 20 wt%.
[0039] Comparative Example 1
[0040] Dissolve 0.49g of Ni(NO3)2·6H2O in 8mL of deionized water; disperse 2g of γ-Al2O3 in 25mL of water and disperse evenly by ultrasonication. Add Ni(NO3)2·6H2O dropwise into the γ-Al2O3 dispersion under stirring, and ultrasonicate for 5 minutes; then freeze-dry the suspension to obtain a Ni / Al2O3 catalyst precursor;
[0041] The catalyst was calcined at 500°C for 4 h and pre-reduced with 40 mL / min of H2 at 500°C for 2 h to obtain a Ni / Al2O3 catalyst with a Ni content of 5 wt%.
[0042] Comparative Example 2
[0043] Dissolve 0.49g of Ni(NO3)2·6H2O in 8mL of deionized water; disperse 2g of CeO2 in 25mL of water and disperse evenly by ultrasonication. Add Ni(NO3)2·6H2O dropwise into the CeO2 dispersion under stirring, and ultrasonicate for 5 minutes; then freeze-dry the suspension to obtain a Ni / CeO2 catalyst precursor;
[0044] The catalyst was calcined at 500°C for 4 h and pre-reduced with 40 mL / min of H2 at 500°C for 2 h to obtain a Ni / CeO2 catalyst with a Ni content of 5 wt%.
[0045] Comparative Example 3
[0046] Dissolve 0.49g of Ni(NO3)2·6H2O in 8mL of deionized water; disperse 2g of TiO2 in 25mL of water and disperse evenly by ultrasonication. Add Ni(NO3)2·6H2O dropwise to the TiO2 dispersion under stirring, and ultrasonicate for 5 minutes; then freeze-dry the suspension to obtain a Ni / TiO2 catalyst precursor;
[0047] The catalyst was calcined at 500°C for 4 h and pre-reduced with 40 mL / min of H2 at 500°C for 2 h to obtain a Ni / TiO2 catalyst with a Ni content of 5 wt%.
[0048] Comparative Example 4
[0049] Dissolve 0.49g of Ni(NO3)2·6H2O in 8mL of deionized water; disperse 2g of ZnO in 25mL of water and disperse evenly by ultrasound. Add Ni(NO3)2·6H2O dropwise to the ZnO dispersion under stirring, and perform ultrasound treatment for 5 minutes; then freeze-dry the suspension to obtain a Ni / ZnO catalyst precursor;
[0050] The Ni / ZnO catalyst with a Ni content of 5 wt% was obtained by high-temperature calcination at 500°C for 4 h and pre-reduction treatment with 40 mL / min of H2 at 500°C for 2 h.
[0051] Comparative Example 5
[0052] Dissolve 0.49g of Ni(NO3)2·6H2O in 8mL of deionized water; disperse 2g of ZrO2 in 25mL of water and disperse evenly by ultrasonication. Add Ni(NO3)2·6H2O dropwise into the ZrO2 dispersion under stirring and perform ultrasonication for 5 minutes; then freeze-dry the suspension to obtain a Ni / ZrO2 catalyst precursor;
[0053] The catalyst was calcined at 500°C for 4 h and pre-reduced with 40 mL / min of H2 at 500°C for 2 h to obtain a Ni / ZrO2 catalyst with a Ni content of 5 wt%.
[0054] Comparative Example 6
[0055] Dissolve 0.43g of H2PtCl6 in 8mL of deionized water; disperse 2g of SiO2 in 25mL of water and disperse evenly by ultrasonication. Add H2PtCl6 dropwise to the SiO2 dispersion under stirring and perform ultrasonic treatment for 5 minutes; then freeze-dry the suspension to obtain a Pt / SiO2 catalyst precursor;
[0056] The catalyst was calcined at 500°C for 4 h and pre-reduced with 40 mL / min of H2 at 300°C for 2 h to obtain a Pt / SiO2 catalyst with a Pt content of 5 wt%.
[0057] Comparative Example 7
[0058] Dissolve 0.20g of RuCl3 in 8mL of deionized water; disperse 2g of SiO2 in 25mL of water and disperse evenly by ultrasonication. Add RuCl3 dropwise into the SiO2 dispersion under stirring and ultrasonicate for 5 minutes; then freeze-dry the suspension to obtain a Ru / SiO2 catalyst precursor;
[0059] The Ru / SiO2 catalyst with a Ru content of 5 wt% was obtained by calcination at 500°C for 4 h and pre-reduction with 40 mL / min of H2 at 300°C for 2 h.
[0060] Comparative Example 8
[0061] Dissolve 0.49g of Co(NO3)2·6H2O in 8mL of deionized water; disperse 2g of SiO2 in 25mL of water and disperse evenly by ultrasonication. Add Co(NO3)2·6H2O dropwise to the SiO2 dispersion under stirring, and ultrasonicate for 5 minutes; then freeze-dry the suspension to obtain a Co / SiO2 catalyst precursor;
[0062] The catalyst was calcined at 500°C for 4 h and pre-reduced with 40 mL / min of H2 at 500°C for 2 h to obtain a Co / SiO2 catalyst with a Co content of 5 wt%.
[0063] Comparative Example 9
[0064] Dissolve 0.43g of H2IrCl6 in 8mL of deionized water; disperse 2g of SiO2 in 25mL of water and disperse evenly by ultrasonication. Add H2IrCl6 dropwise to the SiO2 dispersion under stirring, and ultrasonicate for 5 minutes; then freeze-dry the suspension to obtain an Ir / SiO2 catalyst precursor;
[0065] After high-temperature calcination at 500°C for 4h and pre-reduction treatment with 40mL / min of H2 at 300°C for 2h, an Ir / SiO2 catalyst with an Ir content of 5wt% was obtained.
[0066] Comparative Example 10
[0067] Dissolve 0.18g of PdCl2 in 8mL of deionized water; disperse 2g of SiO2 in 25mL of water and disperse evenly by ultrasonication. Add PdCl2 dropwise into the SiO2 dispersion under stirring and ultrasonicate for 5 minutes; then freeze-dry the suspension to obtain a Pd / SiO2 catalyst precursor;
[0068] The catalyst was calcined at 500°C for 4 h and pre-reduced with 40 mL / min of H2 at 300°C for 2 h to obtain a Pd / SiO2 catalyst with a Pd content of 5 wt%.
[0069] Comparative Example 11
[0070] Dissolve 0.20g of RhCl3 in 8mL of deionized water; disperse 2g of SiO2 in 25mL of water and disperse evenly by ultrasonication. Add RhCl3 dropwise into the SiO2 dispersion under stirring and perform ultrasonication for 5 minutes; then freeze-dry the suspension to obtain a Rh / SiO2 catalyst precursor;
[0071] The Rh / SiO2 catalyst with a Rh content of 5 wt% was obtained by calcination at 500°C for 4 h and pre-reduction with 40 mL / min of H2 at 300°C for 2 h.
[0072] Hydrogenolysis performance test:
[0073] 1g of polyolefin plastic (including 0.35g of polyethylene (PE), 0.35g of polypropylene (PP) and 0.3g of polyvinyl chloride (PVC)) and 1g of catalyst were mixed evenly and placed in a reaction tube. H2 was introduced as the reaction gas and the temperature was raised to 280°C. The reaction was carried out for 6h to obtain tail gas containing CH4, HCl and H2. The tail gas was collected and analyzed by gas chromatography after the reaction. The yields of CH4 and HCl and the yields of plastic using Ni / SiO2 catalysts with different Ni contents, other supported Ni catalysts and common precious metal catalysts were obtained. The results of the conversion rate are shown in Table 1, wherein yield: the ratio of the actual production output of the product obtained by inputting a unit amount of raw materials to the theoretically calculated product output; in this system, CH4 yield = actual CH4 mole number obtained / theoretically calculated maximum CH4 output mole number × 100%, HCl yield = actual HCl mole number obtained / theoretically calculated maximum HCl output mole number × 100%; conversion rate = 100% - remaining raw material mole number / input raw material mole number × 100%, and the remaining raw material is determined by collecting the unconverted plastic after the reaction and weighing it.
[0074] Table 1
[0075]
[0076] According to the results in Table 1, the Ni / SiO2 catalyst with a Ni loading of 1-20% in the present application can hydrogenolyze plastics into CH4 and HCl; wherein, when the Ni loading is 5%, compared with Ni catalysts with other carriers, the Ni / SiO2 catalyst has excellent hydrogenolysis performance and can obtain CH4 and HCl with high selectivity; Ni / SiO2 catalysts with a loading of 5% and above have very high CH4 and HCl yields, and there is no waste plastic raw material remaining in the system after the reaction, indicating that it can achieve >99% conversion of waste plastics. In order to save costs, the Ni loading in the Ni / SiO2 catalyst of the present application can be controlled within the range of 1-20wt%, preferably, within the range of 5-20wt%.
[0077] Determination of Ni dispersion:
[0078] The dispersion of Ni in the catalyst was tested by the Micromeritics ASAP 2020PLUS instrument, and the H2 chemical adsorption method was used for determination and calculation: after the catalyst was pre-reduced, the hydrogen pressure was controlled at different levels of 0-400 mmHg and the H2 isotherm of the catalyst was recorded (representing the total amount of H2 adsorbed reversibly and irreversibly), and then the catalyst was vacuumed for 30 minutes; the hydrogen pressure was controlled at different levels of 0-400 mmHg again and the H2 isotherm of the catalyst was recorded (representing the total amount of H2 adsorbed reversibly); the difference between the two isotherms was the total amount of H2 adsorbed irreversibly; according to the irreversible adsorption model with a surface substance ratio of Ni:H2=2:1, the amount of Ni on the surface can be calculated; the dispersion of Ni can be obtained by dividing it by the total amount of Ni in the catalyst.
[0079] Determination of Ni particle size:
[0080] Statistical calculations were performed using a transmission electron microscope (TEM) and a FEI Tecnai F20 electron microscope was used for testing. The Ni particle sizes in approximately 60 electron microscope images were counted to obtain a number distribution curve of Ni particle sizes and the average particle size of Ni particles in the catalyst.
[0081] Comparing Ni catalysts with different oxide carriers, the Ni dispersion in the 5% Ni / SiO2 catalyst is about 30%, the particle size is about 5-10nm, and there is no obvious agglomeration before and after the reaction; while the Ni particles in the 5% Ni / CeO2 catalyst are larger, with a particle size of about 20nm, and after the reaction they agglomerate into larger Ni particles; it can be seen that in the present application, the use of a precursor with a NiSiO3 nickel silicate structure has a significant stabilizing effect on small Ni clusters and particles at high temperatures, so that the Ni / SiO2 catalyst of the present application has a catalytic performance with high activity and high stability.
[0082] Anti-HCl poisoning performance test:
[0083] This application conducted a follow-up investigation on the 5% Ni / SiO2 catalyst and studied the correlation between its resistance to HCl poisoning and its reaction performance: in the hydrogenolysis performance test, before evaluating the catalyst activity at a reaction temperature of 280°C, the catalyst was treated with 2% HCl / Ar gas for 1 hour, and then switched to the reaction gas for simultaneous hydrogenolysis of an equal amount of polyolefin plastics. The activity changes of the two catalysts are shown in Table 2.
[0084] Table 2
[0085]
[0086] According to the results in Table 2, the CH4 yields of the two catalysts decreased after treatment, but the 5% Ru / SiO2 catalyst was almost inactivated, while the 5% Ni / SiO2 catalyst still retained about 70% of its initial activity. The above results show that the Ni / SiO2 catalyst has excellent resistance to HCl poisoning and has good stability during the conversion of waste plastic systems containing PVC.
[0087] In summary, the present application uses NiSiO3 structural precursor to prepare Ni / SiO2 catalyst, which can realize the process of direct hydrogenolysis of mixed waste plastics into CH4, achieve plastic conversion rate >99%, CH4 yield of 98% and HCl yield of 99%, and realize one-step conversion of waste plastics containing the toxic element Cl.
[0088] The above description is only a preferred embodiment of the present application and is not intended to limit the protection scope of the present application. Any modification, equivalent replacement, improvement, etc. made within the spirit and principle of the present application are included in the protection scope of the present application.
Claims
1. A Ni / SiO2 catalyst, wherein: The Ni loading in the Ni / SiO2 catalyst is 1-30 wt%.
2. The Ni / SiO2 catalyst according to claim 1, wherein The Ni loading amount is 5-20wt%.
3. The Ni / SiO2 catalyst according to claim 1 or 2, wherein In the Ni / SiO2 catalyst, the Ni dispersion is ≥30% and the Ni particle size is 5-10 nm.
4. A method for preparing a Ni / SiO2 catalyst according to any one of claims 1 to 3, comprising: (1) dissolving Ni(NO3)2·6H2O and Si(OC2H5)4 in an 85-95 vol% ethanol aqueous solution, then heating to 70-90°C, adding an ammonium carbonate solution with a concentration of 0.4-0.6 mol / L, and controlling the pH to 8-9, reacting for 2-6 hours, so that Ni and Si are precipitated to form a solid having a nickel phyllosilicate structure, washing with water, and drying to obtain a precursor of a Ni / SiO2 catalyst; Among them, the ratio of the mass of Ni(NO3)2·6H2O, the mass of Si(OC2H5)4, the volume of ethanol aqueous solution, and the volume of ammonium carbonate solution is (0.01-0.45) g: 1 g: (20-60) mL: (5-40) mL; or, (1') under stirring, a Ni(NO3)2·6H2O aqueous solution with a concentration of 0.01-0.4 g / mL is added dropwise to a SiO2 dispersion with a concentration of 0.04-0.1 g / mL, followed by ultrasonic treatment for 4-6 minutes; the suspension is then freeze-dried to obtain a Ni / SiO2 catalyst precursor; (2) Taking the precursor of the Ni / SiO2 catalyst, calcining and pre-reducing it to obtain the Ni / SiO2 catalyst.
5. The preparation method according to claim 4, wherein The calcination includes calcination at a high temperature of 350-550° C. for 3-6 hours.
6. The preparation method according to claim 4, wherein The pre-reduction comprises: treating with 20-80 mL / min of H2 at 200-600°C for 1-6 hours.
7. The preparation method according to any one of claims 4 to 6, wherein The precursor of the Ni / SiO2 catalyst is a precursor having a nickel phyllosilicate structure.